## A community for students. Sign up today

Here's the question you clicked on:

## kris2685 2 years ago 19 - 3(2x - 1)=7

• This Question is Closed
1. jim_thompson5910

First distribute 19 - 3(2x - 1)=7 19 - 6x + 3 =7 Then combine like terms -6x + 22 = 7 What's next?

2. MikiaseKebede

sub 22 for both side of the equation

3. kris2685

im lost i do not get where the 22 comes from

4. jim_thompson5910

19 + 3 = 22

5. jim_thompson5910

that's after you combine like terms

6. Jameshappy

so -6x +22= 7 -22 -22 --------------- ? There you gp

7. Jameshappy

go*

8. MikiaseKebede

then divide -6x for both side of the equation

9. MikiaseKebede

thx for writing it for me

10. Jameshappy

Your welcome :)

11. MikiaseKebede

no i mean divide -6 for both side of the equation

12. Jameshappy

huh?

13. MikiaseKebede

so we want x to be alone after all we are solving the value of x

14. Jameshappy

i know but im not the one who's asking the question, kris2685 is

15. MikiaseKebede

i need your help writing the equation please

16. MikiaseKebede

ok, i got this

17. Jameshappy

ohh

18. Jameshappy

so what was that? What do you want me to do?

19. kris2685

i got 0

20. MikiaseKebede

yes

21. kris2685

yay im not stupid afte all, im horrible at math

22. MikiaseKebede

I new the answer but it is difficult for me to write the steps on the computer. Thex

23. kris2685

thank you all

24. Jameshappy

Haha then no need for my help :)

25. jim_thompson5910

19 - 3(2x - 1)=7 19 - 6x + 3 = 7 - 6x + 22 = 7 -6x = 7 - 22 -6x = -15 x = -15/(-6) x = 5/2 x = 2.5 I would personally go with x = 5/2, but x = 2.5 works just as well

26. MikiaseKebede

sorry i was wrong

27. MikiaseKebede

sorry, my mestake, but this is the answer x = 2.5

#### Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy